Vanadium distribution following decavanadate administration - S. Soares, Sandra (2012)
An acute exposure of two vanadate solutions— metavanadate and decavanadate—containing different vanadate oligomers, induces different patterns of subcellular vanadium distribution in blood plasma, red blood cells (RBC), and cardiac muscle subcellular fractions of the fish Sparus aurata (gilthead seabream). The highest amount of vanadium was found in blood plasma 1 h after (5 mM) intravenous vanadate administration (295 € 64 and 383 € 104 lg V/g dry tissue, for metavanadate and decavanadate solutions, respectively), being 80-fold higher than in RBC. After 12 h of administration, the amount of vanadium in plasma, as well as in cardiac cytosol, decreased about 50%, for both vanadate solutions. During the period between 1 and 12 h, the ratio of vanadium in plasma/vanadium in RBC increased from 27 to 128 for metavanadate, whereas it remains constant (77) for decavanadate. Both vanadium solutions were primarily accumulated in the mitochondrial fraction (138 € 0 and 195 € 34 ng V/g dry tissue for metavanadate and decavanadate solutions, respectively, after 12 h exposure), rather than in cytosol. The amount of vanadium in cardiac mitochondria was twofold higher than in cytosol, earlier for metavanadate (6 h) than for decavanadate (12 h). It is concluded that, in fish cardiac muscle, the vanadium distribution is dependent on the administration of decameric vanadate, with vanadium being mainly distributed in plasma, before being accumulated into the mitochondrial fraction.